Pengembangan Kakas Bantu Penentu Prioritas Kebutuhan Fungsional Sistem dengan Menerapkan Algoritme Genetik - Moh. Zulfiqar Naufal Maulana; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Functional requirement is a functions that must be had in the system that is being develop. Software requirement must be able to overcome the problems that is being faced by stakeholders so that it can facilitate the work of a stakeholder. Determination of priority requirement is something that can determine which system is useful or even fails in its development. An analyst's mistake in ranking the importance of a requirement often results in failure in the development process due to problems of time and resources. Genetic algorithm is an artificial intelligence method developed to solve complex problems in various sciences, such as mathematics, physics, biology, and so on. The usage of genetic algorithm methods in the process of calculating the priority of this requirement is done by calculating the value of disagreement on a chromosome which is carried out continuously until the optimal priority requirements are obtained. The result of these methods is obtained a system that be able to calculate the priority requirements that are feasible to use as a reference in ranking system requirements priority.